2021
DOI: 10.21203/rs.3.rs-829556/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced photocatalytic removal of nitric oxide over Ag-decorated ZnSn(OH)6 microcubes

Abstract: Presently, most of the population has been facing a string of severe climate change problems that primarily come from the intensive emission of nitric oxide (NO), which requires a practical approach to sustain our living conditions. Herein, Ag nanoparticles-decorated ZnSn(OH)6 microcubes (Ag:cZHS) photocatalysts were synthesized rapidly and used for photocatalytic NO removal under solar light activation. The properties of the newly prepared photocatalysts are comprehensively characterized by a series of routin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…On the other hand, for the effect of the single metal to support the photoredox-catalytic NO degradation, our previous study showed a high removal efficiency from the support of Ag NPs. In comparing the previous research and this study, the Au NPs offer higher stability and lower toxical production (Pham et al, 2022). However, the NO removal efficiency of the Au:cZHS was lower than Ag:cZHS.…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…On the other hand, for the effect of the single metal to support the photoredox-catalytic NO degradation, our previous study showed a high removal efficiency from the support of Ag NPs. In comparing the previous research and this study, the Au NPs offer higher stability and lower toxical production (Pham et al, 2022). However, the NO removal efficiency of the Au:cZHS was lower than Ag:cZHS.…”
Section: Resultssupporting
confidence: 53%
“…6(a), the samples strongly absorb photons with a wavelength in the range of UV and visible light (λ > 200 nm). In addition, the peaks in the range of UV light (λ ~340 nm) and visible light (λ ~550 nm) of Au:cZHS can indicate the presence of Au NPs with the surface plasmon resonance (Fu et al, 2021a;Pham et al, 2022). The bandgap of samples was calculated by the Kubelka -Munk plots (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations